Evaluation by extended Hückel method on the hardness of the B–C–N materials - Hideaki Takashima and Yoshinori Kanno (Science and Technology of Advanced Materials, 2005)
Hard materials, e.g. diamond and cubic boron nitride (c-BN), are widely applied to improve the lifetime and the performance of many kinds of cutting and forming tools. These materials are usually used at high temperature, so the study of stability on these materials at high temperature is very important. However, diamond is a low resistance to the oxidation, it should be replaced with the boron-based hard materials. Recently, boron–carbon–nitrogen (B–C–N) ternary materials are expected to possess a high hardness, a high thermal stability at high temperature. We estimated the hardness and the stability of B–C–N materials at high temperature by the extended Hückel method. The extended Hückel method is one of the molecular orbital calculations and needs the cluster model of materials for the calculation. The cluster model of B–C–N materials was regarded as a zinc blende structure. In the present work, we used two physical quantities, i.e. a cohesive energy and an energy fluctuation, as a measure of hardness and stability of materials. The cohesive energy indicates the coherence of bonds between atoms. The energy fluctuation shows the reactivity of materials. Hardness, structure, solid-state properties and reactivity of materials can be estimated from these physical quantities. When the composition of B–C–N materials was boron: 25 at.%, nitrogen: 25 at.% and carbon: 50 at.%, the cohesive energy was the lowest. This result implies B–C–N ternary materials are not harder than c-BN and/or diamond. Cubic-BN was the lowest energy fluctuation of B–C–N materials, and the energy fluctuation increased as increasing of carbon atom. The reactivity of B–C–N materials was high at a high temperature with an increase of carbon atoms. These results imply that B–C–N materials are not suitable for the hard cutting materials.